Factors and processes of natural environment contamination with substitute waters and petroleum products - Василь Суярко; Олег Улицький; Ольга Сердюкова (Вісник Харківського національного університету імені В.Н. Каразіна. Серія Геологія. Географія. Екологія)
Statement of the problem determine the factors and processes of contamination of the natural environment with secondary stratum waters.